Body diffusion‐weighted imaging using magnetization prepared single‐shot fast spin echo and extended parallel imaging signal averaging. Issue 6 (17th October 2017) - Gibbons, Eric K.; Vasanawala, Shreyas S.; Pauly, John M.; Kerr, Adam B.
Abstract : Purpose: This work demonstrates a magnetization prepared diffusion‐weighted single‐shot fast spin echo (SS‐FSE) pulse sequence for the application of body imaging to improve robustness to geometric distortion. This work also proposes a scan averaging technique that is superior to magnitude averaging and is not subject to artifacts due to object phase. Theory and Methods: This single‐shot sequence is robust against violation of the Carr‐Purcell‐Meiboom‐Gill (CPMG) condition. This is achieved by dephasing the signal after diffusion weighting and tipping the MG component of the signal onto the longitudinal axis while the non‐MG component is spoiled. The MG signal component is then excited and captured using a traditional SS‐FSE sequence, although the echo needs to be recalled prior to each echo. Extended Parallel Imaging (ExtPI) averaging is used where coil sensitivities from the multiple acquisitions are concatenated into one large parallel imaging (PI) problem. The size of the PI problem is reduced by SVD‐based coil compression which also provides background noise suppression. This sequence and reconstruction are evaluated in simulation, phantom scans, and in vivo abdominal clinical cases. Results: Simulations show that the sequence generates a stable signal throughout the echo train which leads to good image quality. This sequence is inherently low‐SNR, but much of the SNR can be regained through scan averaging and the proposed ExtPI reconstruction. In vivo results show that the proposed method is able to provide diffusion encoded images while mitigating geometric distortion artifacts compared to EPI. Conclusion: This work presents a diffusion‐prepared SS‐FSE sequence that is robust against the violation of the CPMG condition while providing diffusion contrast in clinical cases. Magn Reson Med 79:3032–3044, 2018. © 2017 International Society for Magnetic Resonance in Medicine.